Women and Rural Development in Iran: Analysis of the Effect of Socio- Economic Changes on Women’ Work in Agriculture - Dadvar-Khani, Fazileh; Choobchian, Shahla (Ciência e Natura, 2015)
There are a number of observable and marked changes in the economic, social, and also cultural status of women’s life in rural areas. This study investigates factors which influence economic participation of women in north of Iran’s rural areas. The influence of government development policy, such as education and Income generating on rural women was sought and investigated in this study. This study particularly focuses on 3 important factors such as “ family income”, “ women’s education “ and “economic class of family” which represent economic, social and cultural status. The descriptive survey method has been applied in this research. The statistical population was 108682 households, from which 131 families were randomly selected. Data has gathered through questionnaires. The results suggest that However, rural development strategies would solve one problem for the women and create another. This paper argues that although rural development may have been beneficial to women and the society as a whole, it has implications for gender roles that go beyond the purview of women’s empowerment. These symptoms reflect a lack of structured development strategy to create new opportunities in these areas. As a result, despite the increasing in women education and family income there is a high rate of unemployment, because the current development policy clearly has failed to introduce new opportunities for women in labor market.